Detection of Sars-Cov-2 Nucleic Acid by Rt-Pcr in Symptomatic and Asymptomatic Patients in Dhaka, Bangladesh (Stamford Journal of Microbiology, 2024)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is responsible for the underlying etiology of COVID-19, a contagious respiratory disease. Proper diagnosis is required to prevent infection from spreading among persons and communities. Precise viral detection is a prerequisite to control the COVID-19 pandemic. Thus, the objective of this study is the detection of SARS-CoV-2 nucleic acid by Real-Time Reverse Transcription-Polymerase Chain Reaction (Real-Time RT-PCR) method of the suspected symptomatic and asymptomatic individuals in Dhaka, Bangladesh. This research was performed in different local hospitals in Dhaka, Bangladesh from June 2021 to January 2022. Samples from suspected individuals were collected following WHO guidelines. Then the samples were placed into a Viral Transport Medium (3 ml sterile VTM). After vortexing, Sansure Biotech Inc. virus nucleic acid RT-PCR test kits were used for diagnosis. Real-Time RT-PCR method was used to identify the positive and negative results of the samples. A total number of 416 COVID-19-suspected individuals were enrolled in this study; 297 (71%) tested real-time RT-PCR-positive, and 119 (29%) were negative. The test results of patients with COVID-19 symptoms were collected and analyzed. Among the positive samples, the positive rate of male patients was higher than female patients. Between age groups, 20 – 59 has shown the highest positivity rate and the lowest was observed below age group 10. Age distribution and clinical characteristics were compared with the neighboring country’s COVID-19 outbreak survey and found to be quite similar. Real-time RT-PCR for SARS-CoV-2 remains the gold standard identification method to verify COVID-19 cases unless and until the World Health Organization (WHO) recommends any alternative approach. Early detection at the primary level of SARS-CoV-2 may aid the clinicians in treatment of COVID-19. All the necessary guidelines need to be followed even after the post-COVID-19 situation.Stam. J. Microbiol. 2024;14(1):13-17